2019
DOI: 10.1128/mbio.02620-18
|View full text |Cite
|
Sign up to set email alerts
|

Endopeptidase Regulation as a Novel Function of the Zur-Dependent Zinc Starvation Response

Abstract: Bacteria encode a variety of adaptations that enable them to survive during zinc starvation, a condition which is encountered both in natural environments and inside the human host. In Vibrio cholerae, the causative agent of the diarrheal disease cholera, we have identified a novel member of this zinc starvation response, a cell wall hydrolase that retains function and is conditionally essential for cell growth in low-zinc environments. Other Gram-negative bacteria contain homologs that appear to be under simi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Although the underlying molecular mechanisms remain unclear, media osmolarity affects the growth of cells harboring conditional mutants of division genes, dictates essentiality of FtsEX for division, and modulates cell size in E. coli [47,87,88]. Extracellular metal availability also alters the activity of several nonessential cell wall enzymes [89][90][91]. Improved understanding of how extracellular processes cope with dynamic environments promises to shed light on how single celled organisms survive-and thrive-across a wide range of ecological niches.…”
Section: The Physical and Chemical Environment As A Mediator Of Extramentioning
confidence: 99%
“…Although the underlying molecular mechanisms remain unclear, media osmolarity affects the growth of cells harboring conditional mutants of division genes, dictates essentiality of FtsEX for division, and modulates cell size in E. coli [47,87,88]. Extracellular metal availability also alters the activity of several nonessential cell wall enzymes [89][90][91]. Improved understanding of how extracellular processes cope with dynamic environments promises to shed light on how single celled organisms survive-and thrive-across a wide range of ecological niches.…”
Section: The Physical and Chemical Environment As A Mediator Of Extramentioning
confidence: 99%
“…The functional consequence of this redundancy remains unclear. In several studies, specific functions of PG hydrolases have been revealed (Nambu et al, 1999;Peters et al, 2016;Santin and Cascales, 2017;Murphy et al, 2019). For example, FlgJ is a lytic transglycosylase that specifically functions to form a hole in the PG that is necessary for late flagella assembly (Nambu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of EPs to efficiently degrade PG poses an exceptional danger to cells. Indeed, purified ShyA almost completely digests purified PG sacculi in vitro (23) through its D,D-endopeptidase activity (42), and the EPs play a crucial role in cell wall degradation as a downstream consequence of exposure to β-lactam antibiotics (27,30). Interestingly, we found that overproduction of V. cholerae's two principal LysM/M23 EPs did not cause any obvious adverse growth phenotypes ( Fig.…”
Section: Genetic Evidence Suggests That Lysm/m23 Endopeptidases Arementioning
confidence: 78%
“…Functional expression of both EPs was verified either by western blot (ShyA only) (SI Appendix, Fig. S1A) or via the ability to complement an EP depletion mutant (ShyA and ShyC) (42). Thus, EP-mediated PG cleavage activity is either tightly regulated in vivo or always outpaced by a highly effective cell wall synthesis machinery.…”
Section: Genetic Evidence Suggests That Lysm/m23 Endopeptidases Arementioning
confidence: 99%
See 1 more Smart Citation